The Influence of Organizational Culture on The Quality of Management Accounting Information Systems and Its Impact on Managerial Performance - Uswatun Hasanah; Dwioctavia Ningrum; Indri Alya Rahayu (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Organizational culture is an important environmental problem for an organization. Managers must understand that culture is an important determinant that affects how well the organization will perform, then. Information systems must be managed based on appropriate methods and methods to strengthen the assumption that the accounting information system implemented by management will affect company performance and that management accounting information systems are not bound by formal criteria that can explain the nature of the input, process, and output. This study aims to determine the effect of organizational culture on the quality of management accounting information systems and its impact on managerial performance. This study uses a causal relationship (cause and effect). The data were collected using a survey method by distributing questionnaires directly to the Bhayangkara Tk Hospital. II Sartika Asih Bandung. The sampling technique was processed using cluster random sampling, amounting to 90 respondents, the data analysis was processed using SEM-PLS using explanatory research. The results obtained indicate that organizational culture has an effect on the quality of the management accounting information system and the quality of the management accounting information system has an effect on managerial performance.